Development of dehydrated grated squash as Vitamin A-Enriched snack food - Lacsamana, Janis Tiu (1998.)
In response to the worsening vitamin A deficiency problem, the development of dehydrated grated squash as vitamin A-enriched snack food was investigated. Samples of dehydrated grated squash pre-treated with varying sulfite concentrations and lengths of steam blanching time were prepared and subjected to sensory evaluation to determine the optimum pre-treatment combination. The selected pre-treatment combination was 0.1% Na₂S₂O₅ and 1 min blanching with an overall acceptability of 6.9 corresponding to the description "like moderately". Vitamin A analysis by HPLC performed on the dehydrated grated squash showed that there was a negligible vitamin A content (0.1ppm) in the product, possibly due to β-carotene oxidation and severely reduced Aw during dehydration. Proximate analysis showed that dehydrated grated squash contains 4.84% moisture, 0.39% crude fat, 0.79% crude protein, 77.08% total available carbohydrates, 1.66% crude fiber and 15.24 ash. Incorporation of cheese flavor and vitamin A fortificant was done dehydrated grated squash and subjected to sensory evaluation. The selected level of incorporation was 5g cheese flavor and 0.774 g fortificant per ml canola oil per 30 g dehydrated grated squash with an average overall acceptability rating (from two production runs) of 6.6 corresponding "like moderately". A serving of 5 g of this product could provide a third of the Recommended Daily Allowance (RDA) for 10-70+ year-old.
Thesis ()BSFT)--University of the Philippines Diliman
Keywords: Squash, Dried; Enriched foods